The Prevalence of Killer Yeasts in the Gardens of Fungus-Growing Ants and the Discovery of a Novel Killer Toxin named Ksino - Bizarria, Rodolfo [UNESP]; Creagh, Jack W.; dos Santos, Renato A. Corrêa; LGivens, Lily; Coss, Sarah A.; Badigian, Tanner J.; Chavez, Adrian V.; Tekle, Rim T.; Fredstrom, Noah; Ytreberg, F. Marty; Dunham, Maitreya J.; Rodrigues, Andre [UNESP]; et al. (Cold Spring Harbor Laboratory, 2024)
Killer toxins are proteinaceous antifungal molecules produced by yeasts, with activity against a wide range of human and plant pathogenic fungi. Fungus gardens of attine ants in Brazil were surveyed to determine the presence of killer toxin-producing yeasts and to define their antifungal activities and ecological importance. Our results indicate that up to 46% of yeasts isolated from specific fungal gardens can be killer yeasts, with an overall prevalence of 17% across all strains tested. Killer yeasts were less likely to inhibit the growth of yeasts isolated from the same environment but more effective at inhibiting yeast isolated from other environments, supporting a role for killer yeasts in shaping community composition. All killer yeasts harbored genome-encoded killer toxins due to the lack of cytoplasmic toxin-encoding elements (i.e., double-stranded RNA satellites and linear double-stranded DNAs). Of all the killer yeasts identified, an isolate of Candida sinolaborantium showed a broad spectrum of antifungal activities against 57% of yeast strains tested for toxin susceptibility. The complete genome sequence of C. sinolaborantium identified a new killer toxin, Ksino, with primary and tertiary structure homology to the Saccharomyces cerevisiae killer toxin named Klus. Genome-encoded homologs of Ksino were found in yeast strains of Saccharomycetes and Pichiomycetes, as well as other species of Ascomycota and Basidiomycota filamentous fungi. This demonstrates that killer yeasts can be widespread in attine ant fungus gardens, possibly influencing fungal community composition and the importance of these complex microbial communities for discovering novel antifungal molecules.